Penerapan E-Commerce dan Pengemasan Safety Food sebagai Strategi Peningkatan Pemasaran Produk Kue Kering Khas Cirebon - Chairun Nas; Linda Norhan; Wiwiek Nurkomala Dewi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
As the cost of living increases, people have begun to establish home-based businesses to meet their daily needs. JP Snack is a small home business that produces traditional Cirebon cookies. Currently, their products are sold through third parties, namely sellers in various traditional market shops. Due to the Covid-19 pandemic from 2020 to 2022, consumer shopping habits shifted from conventional to online shopping via E-Commerce, leading to a decline in JP Snack’s sales. Additionally, the product's packaging was deemed unsafe, with a shelf life of only 2 months. The packaging also appeared outdated, making it seem like a snack for older generations, particularly among millennials. To address these issues, JP Snack needs to market its products online and improve its packaging design. The goal of this community service activity is to create an E-Commerce application to help the business market its products widely and develop safety food packaging to ensure product durability and appeal. The E-Commerce platform includes features like promotions, chat, ratings, and testimonials to boost consumer trust. Moreover, the packaging is updated with a modern design using standing pouches with zipper locks. As a result, JP Snack products have been ordered by customers from other provinces, and the safety food packaging extends shelf life to 4 months.